Odpowiedzi

Najlepsza Odpowiedź!
2010-02-20T16:57:38+01:00
1) Pc= 4*a*h/2
Pc= 4*6*3pierwiastki z 3/2=36pierwiastki z 3

V= 1/3Pp*H
Pp= 3pierwiastki z 3*6/2=9pierwiastki z 3
H^2=3^2+(3pierwiastki z3)^2
H^2=27-9
H^2=3pierwiastki z 2
V= 1/3*9pierwaistki z 3*3pierwiastki z 2= 9pierwiastków z 6

2)Pp= 6*2*pierwiastek z3/2=6pierwiastków z 3
Pb= 6*2*pierwiastk z 11/2= 6pierwiastków z 11
Pc= 6pierwiastków z 3+6pierwiastków z 11

V= 1/3Pp*H

2^2+H^2=6^2
H^2=32
H= 4pierwiastki z 2

V= 1/3*6pierwiastków z 11*4pierwiastki z 2= 8pierwiastków z 22



20 2 20